100 American crime writers - Powell, Steven, 1983- (Crime files series., 2012)
From Edgar Allan Poe to James Ellroy, crime writers have provided some of the most popular, controversial, acclaimed and disturbing works in American literature. 100 American Crime Writers provides critical biographies of some of the greatest and most important crime writers in American history. Both an important scholarly work and an enjoyable read accessible to a wider audience, this addition in Palgrave's Crime Files series includes discussion of the lives of key crime writers, as well as analysis of the full breadth and scope of the genre - from John Dickson Carr's Golden Age detective stories to Raymond Chandler's hardboiled Philip Marlowe novels, Ed McBain's 87th Precinct police procedurals to Megan Abbott's modern day reimagining of the femme fatale. Drawing on some of the best and most recent scholarship in the field, all of the key writers and themes of the genre are discussed in this comprehensive study of one of the most fascinating and popular of literary genres.